Early childhood educators’ experiences with and perspectives of the Early Learning and Child Care Supplement in the Province of Newfoundland and Labrador - Melissa Lynn Russell (10847964) (2020)
This major research paper presents findings from a qualitative study with eight early childhood educators working in licensed childcare settings in St. John's Newfoundland and Labrador. The study used the political economy of care and feminist ethics of care theory to interpret participants' experiences with and perspectives of the Early Learning and Child Care (ELCC) Supplement in the province of Newfoundland and Labrador. Based on participants' views, this study's primary findings suggest that participants perceived the ELCC Supplement as an incentive or bonus to top off the low wages of an early childhood educator. Second, participants articulated a shared appreciation of some features of the ELCC Supplement. At the same time, they asserted several dislikes. As we dug deeper, participants reported a significant number of abuses in the distribution of the ELCC Supplement. Finally, the participants shared their thoughts on recommendations for changes to be made to the ELCC Supplement. Key words: Early learning and child care supplement, early childhood educator, early childhood education and care, childcare, care, carework, political economy of care, feminist ethics of care